Analysis of images, social networks and texts : 4th International Conference, AIST 2015 Yekaterinburg, Russia, April 9-11, 2015 : revised selected papers /: 4th International Conference, AIST 2015 Yekaterinburg, Russia, April 9-11, 2015 : revised selected papers. (2015) - Unknown
No abstract available